“Longing is good”: proof-of-concept for a novel psychological intervention to tackle self-blaming emotions - Lajmi, Nahed; Duan, Suqian; Moll, Jorge; Zahn, Roland (Frontiers in Psychology, 2025)
BackgroundMany people with depression, for which self-blame plays a key role, are not amenable to current standard psychological treatments. This calls for novel self-guided interventions, which require less attention and motivation. The present study sought to establish proof-of-concept for a novel self-guided intervention in a non-clinical sample, which prompts people to transform self-blaming feelings into “longing,” as a related unpleasant, but presumably more adaptive and approach-related emotion, which plays a key role in many musical and literary genres but has been largely overlooked in clinical research.MethodsThirty nine participants with no previous self-reported history of mental disorders, but who experienced frequent feelings of self-blame were enrolled remotely (n = 3 lost to follow-up). Self-blaming thoughts, along with depressive symptoms and other outcomes, were assessed pre- and post-intervention to determine the potential of the intervention, which consisted of creating a 10-min video starting with self-blame evoking materials, transitioning to sadness and finally longing. Participants were then asked to watch their video daily for 7 days.ResultsThe number of participants lost to follow-up was low (n = 3) and engagement with the intervention was very high. As predicted, the intervention significantly reduced depressive symptoms on our primary outcome measure (Beck’s Depression Inventory, BDI-II, Cohen’s d = 0.40) after 1 week. This was further confirmed by a reduction on the Maudsley-modified Patient Health Questionnaire-9. Unexpectedly, no changes were observed on the non-clinical measures.LimitationsA randomized controlled trial design is needed to determine whether these symptom reductions were causally related to the intervention. Additionally, our findings may not generalize to men, due to our inability to recruit a sex-balanced sample.ConclusionAs predicted, participants benefited from being prompted to transform self-blaming feelings into those related to longing which shows the feasibility and potential to be further developed in people with clinical depression. Our study highlights the adaptive potential of unpleasant approach-related emotions such as longing, which are rarely considered in standard psychotherapies.